The linguistic turn in hermeneutic philosophy - Lafont, Cristina, 1963- (Studies in contemporary German social thought., 1999)
Annotation The linguistic turn in German philosophy was initiated in the eighteenth century in the work of Johann Georg Hamann, Johann Gottfried von Herder, and Wilhelm von Humboldt. It was further developed in this century by Martin Heidegger, and Hans-Georg Gadamer extended its influence to contemporary philosophers such as Karl-Otto Apel and J?Habermas. This tradition focuses on the world-disclosing dimension of language, emphasizing its communicative over its cognitive function. Although this study is concerned primarily with the German tradition of linguistic philosophy, it is very much informed by the parallel linguistic turn in Anglo-American philosophy, especially the development of theories of direct reference. Cristina Lafont draws upon Hilary Putnam's work in particular to criticize the linguistic idealism and relativism of the German tradition, which she traces back to the assumption that meaning determines reference. Part I is a reconstruction of the linguistic turn in German philosophy from Hamann to Gadamer. Part II offers the deepest account to date of Habermas's approach to language. Part III shows how the shortcomings of German linguistic philosophy can be avoided by developing a consistent and more defensible version of Habermas' theory of communicative rationality.